1995
DOI: 10.1063/1.469606
|View full text |Cite
|
Sign up to set email alerts
|

S 0↔S1 transition of trans-β-methyl styrene: Vibronic structure and dynamics

Abstract: The fluorescence excitation and emission spectra of trans-β-methyl styrene have been measured in a supersonic jet. A complete vibrational assignment of the S0 and S1 states’ frequencies is reported, assisted by ab initio quantum chemical calculations and by comparison with the IR spectrum. The fluorescence lifetime, τf, of the isolated molecule changes monotonously from 24.5 to 15 ns as the excitation energy increases from the origin band to an excess of 3000 cm−1. The fluorescence quantum yield from the zero-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…[3][4][5] It was found that the method is useful for this purpose, as judged by comparison with experimental results. Practical considerations limited the size of the basis set that could be used in these calculations.…”
Section: Introductionmentioning
confidence: 96%
“…[3][4][5] It was found that the method is useful for this purpose, as judged by comparison with experimental results. Practical considerations limited the size of the basis set that could be used in these calculations.…”
Section: Introductionmentioning
confidence: 96%
“…[10][11][12] Phosphorescence has never been detected from photoexcited styrene; however, many studies have suggested that photochemical cis-trans isomerisation mechanisms for styrene proceed via triplet states. 11,[13][14][15] known to have a nanosecond timescale. The only ultrafast decay pathway from S 1 is to S 0 directly via a conical intersection, requiring extra vibrational energy.…”
Section: Introductionmentioning
confidence: 99%
“…The latter molecule was studied in order to assign the jet cooled fluorescence excitation and emission spectra reported in the companion paper. 15 The structures of these molecules and the atom numbering convention are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The low lying electronic states of styrene, which is the simplest molecule containing both an aromatic ring and a double bond, have been extensively studied experimentally 16 -20 and theoretically. [21][22][23][24][25] Experimental data based primarily on UV spectroscopy indicate that the molecule is planar in both the ground and the first electronically excited singlet states.…”
Section: Introductionmentioning
confidence: 99%